2020
DOI: 10.14217/comsec.1066
|View full text |Cite
|
Sign up to set email alerts
|

Preventing and Countering Violent Extremism

Abstract: This document is intended to support departments and officers of the Government of the Republic of Trinidad and Tobago (GoRTT) to effectively engage and capacity-build non-profit organisations (NPOs) for Preventing and Countering Violent Extremism (PCVE) activity.The Framework provides practical advice and guidance on how to engage NPOs, assess and develop the capacity of prospective delivery agencies, co-design interventions and manage risk. All statistics quoted in this document are available in the public d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…125 Notably, while the author found that the results of many studies suggested that educational interventions were beneficial, he was unable to identify studies comparing the outcomes of various interventions. 126 Importantly, the above study concluded that there was a lack of evidence-based interventions that focus on countering/preventing violent extremism. The authors recommended that future researchers consider evaluating the comparative efficacy of interventions.…”
Section: Counselling For Deradicalizationmentioning
confidence: 96%
“…125 Notably, while the author found that the results of many studies suggested that educational interventions were beneficial, he was unable to identify studies comparing the outcomes of various interventions. 126 Importantly, the above study concluded that there was a lack of evidence-based interventions that focus on countering/preventing violent extremism. The authors recommended that future researchers consider evaluating the comparative efficacy of interventions.…”
Section: Counselling For Deradicalizationmentioning
confidence: 96%